The Slow Evolution of CS for All, the Beauty of Programs. - Guzdial, Mark; Hill, Robin K. (Communications of the ACM, 2017)
The article examines issues relating to computer science (CS). Particular focus is given to the steps needed to reach the goals of CS access for all, and to the aesthetics of programming. Additional topics discussed include the Expanding Computing Education Pathways (ECEP) alliance, the President's CS for all initiative in the U.S. and criteria for program elegance including minimality, accomplishment and modesty.